Scoping Review: Self Care Instrument for Chronic Kidney Disease Patients on Hemodialysis - Firah Azzahra; Wahyu Hidayati; Sri Padma Sari (Indonesian Journal of Global Health Research, 2025)
Chronic kidney disease (CKD) is an incurable global health problem, with a growing prevalence, particularly in Asia. It is estimated that by 2030, 2.16 million individuals will require hemodialysis, a 233% increase from previous years. Self-care practices are an important aspect in improving health, preventing complications, and supporting daily functioning and well-being of patients. Therefore, a valid and reliable instrument is needed to measure the level of self-care in patients with chronic diseases. Objective to identify a validated self-care assessment instrument for hemodialysis patients. The methodological approach refers to Arksey and O'Malley, with article searches through ScienceDirect, PubMed, and EBSCO databases using relevant keywords, focusing on full-text, English-language, open access, and published in the last 18 years published between 2007 and 2024, keywords included "self-care", "hemodialysis", "instrument", "scale", and "chronic kidney disease". Of the 1,327 articles screened, the investigation was executed by accumulating empirical data from the preceding 18 years, aggregating 22 scholarly articles, among these, 9 articles satisfied the inclusion criteria, concentrating on selected studies that utilized quantitative methodologies and on self-care instruments for hemodialysis patients. The article evaluation was conducted systematically employing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) as a framework, succeeded by assessment based on inclusion and exclusion criteria. This study identified nine self-care instruments for hemodialysis patients with varying psychometric properties. Most of the instruments showed good reliability and validity, but still require improvement in criterion validation, sensitivity, and responsiveness. Future research should focus on the development of concise yet comprehensive instruments, cross-cultural adaptation, and full psychometric evaluation to ensure accurate measurement of self-care, thereby improving patients' health outcomes and quality of life.